PRACTICAL IMPORTANCE OF PHYSICAL EDUCATION OF STUDENTS IN EDUCATIONAL INSTITUTIONS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article is aimed at educating the students and students studying in the Republic of Uzbekistan on the role and importance of Physical Culture in the education system, and through its training a person not only physically, but also comprehensively. Physical education and mass sports work carried out in educational institutions are also important in the productive use of student-students ' free time, their healthy development. President Sh Mirziyoev Location In the decrees and decrees of the implementation of fundamental and practical research aimed at attracting talented children to sports for physical training and sports, as well as the development and implementation of modern methods of their sorting is a vital necessity.